Effects of guanidinoacetic acid supplementation in all‐plant protein diets on growth, antioxidant capacity and muscle energy metabolism of bullfrog Rana (Lithobates) catesbeiana. (21st September 2017) - Zeng, Qiu‐Hui; Rahimnejad, Samad; Wang, Ling; Song, Kai; Lu, Kangle; Zhang, Chun‐Xiao
Abstract: Effects of guanidinoacetic acid (GAA) supplementation in all‐plant protein diets were evaluated on growth, antioxidant capacity and muscle energy metabolism of Rana ( Lithobates ) catesbeiana . Six diets were prepared: a basal fish meal diet (FM), an all soybean meal diet (SM) and four GAA‐supplemented diets by adding 0.2, 0.4, 0.6 and 0.8 g GAA/kg to the SM diet (GAA2, GAA4, GAA6 and GAA8 diets). Triplicate groups of bullfrog (45 ± 0.2 g) were fed the diets to apparent satiation for 8 weeks. Total substitution of FM with SM led to significantly ( p  <   .05) reduced growth and feed utilization. Adding 0.4 g GAA/kg to the SM diet significantly improved growth performance, and the values were comparable to those of FM group. SM and GAA2 groups showed drastically lower serum total antioxidant capacity than FM, GAA4 and GAA6 groups. Also, SM and GAA2 groups showed significantly lower catalase activity than FM and GAA8 groups. A remarkable increase in serum malondialdehyde concentration was detected in SM and GAA2 groups. FM and GAA6 groups exhibited significantly higher serum creatinine concentration than other groups. Muscle creatine kinase activity and glycogen content were significantly decreased in SM group and application of 0.4–0.6 g GAA/kg significantly improved their values. GAA4 group showed significantly lower pyruvate kinase activity than FM and GAA6 groups. Also, GAA2 and GAA4 groups had significantly lower succinate dehydrogenase (SDH) activity than other treatments. These findings show that supplementing 0.4 g/kg GAA to SM‐based diets improves growth, antioxidant capacity and muscle energy metabolism.